Community Empowerment through Social Change Communication: Creating Environmental Transformation and Sustainability at Masjid Al-Ansor Bukit Kemiling Permai - Zulbilal, Ahmad; Syafril, Syafrimen (The Eastasouth Journal of Social Science and Humanities, 2025)
Indonesia, home to one of the world’s largest Muslim communities, relies on mosques as central hubs for worship and religious gatherings. This community service initiative focuses on the Al-Ansor Mosque in Bukit Kemiling Permai, Bandar Lampung, aiming to address key challenges through hands-on engagement. The approach includes coordinating efforts, executing practical activities, empowering locals, distributing essential cleaning supplies, assessing outcomes, and compiling detailed reports. Several issues were identified: a lack of community involvement in maintaining the worship space, insufficient facilities, and concerns over safety. The team behind this project envisions the Al-Ansor Mosque not just as a place of prayer, but as a clean, secure, and vibrant center for religious and social activities. A well-kept mosque environment plays a vital role in uniting people through shared faith and devotion. By fostering open dialogue and encouraging social change, the team aims to inspire lasting community commitment to the mosque’s upkeep. The ultimate goal is to motivate residents to take greater responsibility for preserving this sacred space, ensuring it remains a cornerstone of spiritual and communal life.